1993
DOI: 10.1016/0378-1097(93)90315-s
|View full text |Cite
|
Sign up to set email alerts
|

Surface films of Escherichia coli colonies

Abstract: Escherichia coli colony surfaces were examined using SEM and TEM. The results indicated that bacterial colonies in the course of their development produce surface films which become thicker with increased growth duration. Membrane vesicles contribute to the formation of the surface film. The complex organization of the film suggests that it may perform specific functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…It is required that the rate of bleb production during exponential growth be proportional to wall turnover and synthesis and to assembly of outer membrane. The presence of membrane vesicles in bacterial colonies has been reported [23]. The bacteria in developed colonies are mixtures of dead cells, division‐arrested cells and actively dividing cells.…”
Section: Resultsmentioning
confidence: 94%
“…It is required that the rate of bleb production during exponential growth be proportional to wall turnover and synthesis and to assembly of outer membrane. The presence of membrane vesicles in bacterial colonies has been reported [23]. The bacteria in developed colonies are mixtures of dead cells, division‐arrested cells and actively dividing cells.…”
Section: Resultsmentioning
confidence: 94%
“…Other studies have shown that at later stages of colony development (20 to 24 h), the surface film of E. coli colonies became thicker. On the other hand, the film was not observed for colonies cultured for 6 to 16 h of growth (45)(46)(47)(48). Therefore, it is possible that the glycogen-rich surface layer observed with Raman microspectroscopy is the polysaccharide-rich extracellular coat, commonly known as the glycocalyx, of bacterial cells.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the extracellular DNA in the biofilm matrix could take part in the development of bacterial communities (25,40,49,63). It can be released by live cells, possibly via membrane vesicles composed of bacterial lipids (65), or it may enter the matrix from lysed cells (10,18,19,48,58,65). We have recently found cell-free DNA as a component of EPS in biofilms formed by various unrelated gram-positive and gramnegative bacteria and fungi (G. Tetz and V. Tetz, unpublished data).…”
mentioning
confidence: 99%